Me and the Mosque: By Zarqa Nawaz, author and director (National Film Board of Canada, 2005. 52 minutes.) (American Journal of Islam and Society, 2006)
Zarqa Nawaz is a Canadian Muslim filmmaker who lives with her family inRegina, Saskatchewan. There are any number of comments that could beinserted at this point. Having spent time on both the Saskatchewan andManitoba prairies, I note only that Zarqa is developing a television series forthe Canadian Broadcasting Corporation entitled “Little Mosque on thePrairie.” She has made two earlier short films, BBQ Muslims and DeathThreat. Information about those films, as well as about Zarqa, can be foundon her website, Fundamentalist Films, available at www.fundamentalistfilms.com.Me and the Mosque, her first documentary, is distributed by the NationalFilm Board of Canada. The film is directly related to her own concerns as aMuslim woman, namely, as to space available to her in the mosque. The filmbegins on a light-hearted note (as does her web site, with the tag line of “puttingthe fun back into fundamentalism”) with Muslim comic Azhar Usmanjoking about the lack of appropriate space available in mosques for Muslimwomen.The documentary traverses mosques in Canada and the United States,such including places as Aurora, Illinois; Mississauga, Ontario; Winnipeg,Manitoba; Regina, Saskatchewan; Surrey, British Columbia; and Morgantown,West Virginia. It includes the voices of established scholars, amongthem Asma Barlas, Umar Abd-Allah, and Aminah McCloud, alongside thenewer scholarly voices of Aisha Geissinger, Jasmine Zine, and Itrath Syed.In addition, there is a wide range of interviews with people from the Muslimcommunity, from such activists as Asra Nomani and Aminah Assilmi to suchscholars as Abdullah Adhami and Tareq Suwaidan.As mentioned above, the film begins on a humorous note with the comedyof Azhar Usman (of “Allah Made Me Funny” fame). However, what hejokes about, the nice “dungeons” that many people mention when they talkabout the basements where some mosques give space to women, is no laughingmatter. The film then moves to the mosque in Aurora to begin its discussionof these issues. I would like to think that this is Zarqa’s subtle homageto another Canadian filmmaker, Mike Myers, who bases his fictional character,Wayne Campbell, in Aurora. Zarqa then mentions her upbringing inToronto and contrasts the mosque that she attended (the Jami’ Mosque) while ...